2022
DOI: 10.15212/cvia.2022.0011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Loading-Dose Statins Combined with PCSK9 Inhibitor Pre-Treatment before Primary Percutaneous Coronary Intervention on the Short-Term Prognosis in Patients with ST-Segment Elevation Myocardial Infarction

Abstract: Objective: This study was aimed at investigating the effects of preoperative treatment with a loading dose of statinscombined with a PCSK9 inhibitor on coronary blood perfusion and short-term cardiovascular adverse events in patientswith ST-segment elevation myocardial infarction (STEMI).Method: Sixty-five patients with STEMI who had visited the Shanxi Cardiovascular Disease Hospital between May2018 and May 2021 were enrolled in the study. The enrolled patients had no history of oral statins or antiplatelet th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The corrected TIMI frame count (CTFC) index was significantly lower in the test group immediately after PCI and 30 days after PCI, while the TIMI myocardial perfusion grading (TMPG) index was higher than in the control group (35). However, the treatment did not decrease the incidence of cardiovascular death, non-fatal myocardial infarction, or target vessel revascularization (35).…”
Section: Early Pcsk9 Inhibitors and Coronary Imaging Changesmentioning
confidence: 92%
See 3 more Smart Citations
“…The corrected TIMI frame count (CTFC) index was significantly lower in the test group immediately after PCI and 30 days after PCI, while the TIMI myocardial perfusion grading (TMPG) index was higher than in the control group (35). However, the treatment did not decrease the incidence of cardiovascular death, non-fatal myocardial infarction, or target vessel revascularization (35).…”
Section: Early Pcsk9 Inhibitors and Coronary Imaging Changesmentioning
confidence: 92%
“…The GLAGOV study ( n = 968) suggested that PCSK9 inhibitors could promote regression in plaque composition ( 33 , 50 ). Studies are underway to determine the effects of the early implementation of PCSK9 inhibitors on plaque, blood flow, vascular inflammation, and other relevant imaging features in patients with ACS ( 13 , 15 , 34 , 35 , 51 ).…”
Section: Early Pcsk9 Inhibitors and Coronary Imaging Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Due in part to the rapid and profound reduction in LDL-C with in-hospital administration of PCSK9i, as well as challenges with attaining target LDL-C with statins alone [14], several small trials have demonstrated plaque regression and stabilization with PCSK9i. Relative to standard of care with statin with or without ezetimibe, addition of PCSK9i leads to a reduction in the lipid content, stabilization of plaque through increased thickening of the fibrinous cap, and reduction in atheroma volume [17 ▪▪ ,23 ▪▪ ,24,25,26 ▪ ,27 ▪ ,28–30,31 ▪ ] that is evident as soon as 30 days later (Table 1). These findings were confirmed in a meta-analysis that showed a consistent, significant regression, and stabilization of plaque by a variety of measurement modalities [32].…”
Section: Pcsk9 Inhibitors In Patients With Acute Coronary Syndromesmentioning
confidence: 99%